Perancangan Sistem Tata Udara dengan Software Bry-Air pada Ruang Kamar Tidur di Bogor, Indonesia - Soewono, Arka Dwinanda; Alferio, Gavin; Darmawan, Marten (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2023)
An effective and efficient air system can provide optimal comfort and health for room occupants. This research uses Bry-Air Software to design an integrated air conditioning system that can improve comfort and health by considering temperature, humidity, air circulation, and air cleanliness. The design was carried out for a bedroom measuring 3 m x 3 mx 3 m using ASHRAE standards where the ideal room temperature is in the range of 23 ± 2°C, relative humidity 55 ± 5%, and ideal airflow of 108 Cubic Meters per Hour (CMH). ISO class 8 requirements with a maximum particle number of 100,000 particles/ft3 for a particle size of 0.5 µm are also used as a criteria during the design process to ensure clean air for room occupants. Simulation results from Bry-Air Software in accordance with ASHRAE and ISO standards found that the room needs to be equipped with a single Air Conditioner (AC) units with a capacity of ½ PK each, 1 Dehumidifier unit with a capacity of 51 CMH and an Air Cleaner with Pre-Filter and Medium Filter. The results of this research hopefully can contribute to developing integrated air conditioning systems for the comfort and health of building occupants in Indonesia.